Unlocking iron: nutritional origins, metabolic pathways, and systemic significance - Malik, Zoha Imtiaz; Ghafoor, Muhammad Umer; Shah, Syed Hassan Bin Usman; Abid, Juweria; Farooq, Umar; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
Iron is a vital micronutrient, involved in numerous cellular functions including DNA synthesis, oxygen transport, energy generation, and immunity enhancement. It has unique redox properties that make it necessary for multiple metabolic reactions. However, the same property warrants its tight regulation as well. Despite its widely acknowledged role in biological sciences, iron deficiency remains one of the leading micronutrient deficiencies across the globe. Understanding iron’s multifaceted roles, mechanisms of systemic regulation, and nutriture assessment, can better guide public health interventions aimed at restoring iron status in at-risk population groups. This review aims at providing a comprehensive analysis of iron’s dietary sources, metabolic role, physiological functioning, absorption enhancers and inhibitors, and systemic regulation, such as hepcidin’s role in iron homeostasis. It further evaluates commonly utilized iron assessment indicators including serum ferritin, transferrin saturation, soluble transferrin receptor, and hemoglobin their uses and limitations, particularly in the context of inflammation. Iron’s metabolic roles are closely tied to its bioavailability and transportation within the body. Nutrient interactions, regulator pathway dysregulation, and dietary pathways, all significantly affect iron status. Available iron assessment indicators are valuable but research is required to interpret findings in inflammatory states. Advancement of integrated iron assessment strategies and metabolic roles can help address iron-related disorders more effectively.